2016
DOI: 10.21831/jipi.v2i2.8561
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan project based learning terintegrasi STEM untuk meningkatkan literasi sains siswa ditinjau dari gender

Abstract: AbstrakPenelitian ini bertujuan untuk menyelidiki pengaruh gender siswa terhadap literasi sains melalui pembelajaranproject based learning (PjBL) yang diintegrasikan dengan science, technology, engineering, dan mathematics (STEM) pada tema pencemaran udara. Metode penelitian yang digunakan adalah pre-eksperimen dengan desain The static Group Pretest-Posttest Designyang dilaksanakan di kelas VII SMP Islam Terpadu di kabupaten Sukabumi sebanyak 57 siswa yang terdiri dari kelas laki-laki (29 orang) dan kelas pere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
141
1
63

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(213 citation statements)
references
References 1 publication
8
141
1
63
Order By: Relevance
“…Menurut Afriana (2016) Based Learning merupakan proyek yang memfokuskan pada pengembangan produk atau unjuk kerja (Performance), siswa melakukan kegiatan mengorganisasikan kegiatan belajar kelompok, melakukan pengkajian atau penelitian, memecahkan masalah, dan mensistesis informasi. Project Based Learning merupakan pendekatan pembelajaran yang memberikan kebebasan kepada peserta didik untuk merencanakan aktivitas belajar, melaksanakan proyek secara kolaboratif, dan pada akhirnya menghasilkan produk kerja yang dapat dipresentasikan kepada orang lain (Nurohman, 2007).…”
Section: Pendahuluanunclassified
“…Menurut Afriana (2016) Based Learning merupakan proyek yang memfokuskan pada pengembangan produk atau unjuk kerja (Performance), siswa melakukan kegiatan mengorganisasikan kegiatan belajar kelompok, melakukan pengkajian atau penelitian, memecahkan masalah, dan mensistesis informasi. Project Based Learning merupakan pendekatan pembelajaran yang memberikan kebebasan kepada peserta didik untuk merencanakan aktivitas belajar, melaksanakan proyek secara kolaboratif, dan pada akhirnya menghasilkan produk kerja yang dapat dipresentasikan kepada orang lain (Nurohman, 2007).…”
Section: Pendahuluanunclassified
“…Gunawan, Sahidu, Harjono, & Suranti (2017) produced the same findings that learning using projects can increase students' creativity. While the findings of Afriana, Permanasari, & Fitriani (2016) show that projectbased learning can improve students' scientific literacy skills. The development of creative thinking skills and scientific literacy of students during the project learning process is trained consistently and continuously by providing problems that must be solved by producing a product based on scientific literature obtained by students.…”
Section: Discussionmentioning
confidence: 97%
“…This is also supported by data from interviews to two teachers of physics at Senior High School in Lampung Province of Indonesia which revealed that the level of scientific literacy of students is still low, this is indicated in the low-skill students in solving the problems associated with the application in daily life. The research results from (Afriana, Permanasari, & Fitriani, 2017) reveal that many students in Indonesia are not able to relate the science knowledge they had learned with the phenomena that occur in the world, because they do not gain experience to associate it.…”
Section: Introductionmentioning
confidence: 99%
“…One of the solutions is Sains, Technology, Engineering, Mathematics (STEM) learning approach that provides opportunities for teachers to demonstrate to students the concepts, principles, science, technology, engineering, and mathematics integrated into the development of products, processes, and systems used in their daily lives. The definition of STEM education as an interdisciplinary approach to learning is where the students use science, technology, engineering, and mathematics in real contexts that connect between school, work, and global world, thus, developing STEM literacy that enables the students to compete in the new era of knowledge-based economy (Afriana, Permanasari, & Fitriani, 2016). Education in science, mathematics, engineering, and technology (STEM) is widely recognized as a pressing state and national priority (Honey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%